The Challenges Faced by Computer Science Students in Understanding Physics - Syahid, Jihad; Nasution, Adelyna Oktavia (Bahasa Indonesia, 2025)
Physics is a fundamental course taught to Computer Science students at the university level, even though it is not directly related to programming. This study aims to identify the challenges faced by students in understanding Physics, analyze the causes of these difficulties, and evaluate students' perceptions regarding the relevance of Physics in the field of Computer Science. The research employed a descriptive quantitative method using a Google Form questionnaire. A total of 30 Computer Science students from the State Islamic University of North Sumatra participated as respondents. The results show that most students experience difficulties in understanding Physics, mainly due to the abstract nature of the material, lack of practice (78.8%), and explanations that are not contextual. Many students also felt that their Physics skills had not significantly improved during their studies. Nevertheless, they acknowledged the importance of Physics, especially in fields such as robotics, simulation, and game development. Respondents also expressed enthusiasm for contextual and digitally supported learning approaches. Proposed solutions include implementing contextual learning that connects Physics to Computer Science applications, utilizing visual media and simulations, and improving pedagogical training for lecturers. These approaches are expected to enhance comprehension, interest, and the perceived relevance of Physics among Computer Science students.